PROGRAM PELATIHAN DIVERSIFIKASI PRODUK OLAHAN PISANG DI KELURAHAN ROWOSARI KECAMATAN TEMBALANG KOTA SEMARANG SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT SETEMPAT - Patricia Dhiana Paramita; Agustien Zulaidah (Majalah Ilmiah Inspiratif, 2021)
Banana commodities can be excellent and superior products from Rowosari Village, TembalangDistrict, Semarang City, if it can be managed properly. However, unfortunately, during this time the Rowosari Village community, which is the location of the Semarang Pandanaran University Community, is quite satisfied by relying on the sale of bananas as they are. on the market. Though these bananas can be processed into other processed products, both food and beverages that have use value and economic value and are able to sell higher than the original products that can improve the welfare of the local community. The aim of Community Service is to improve the quality and quantity of bananas, diversify products and expand the marketing network of banana processed products by cooperating with various parties. There needs to be ongoing assistance by the Pandanaran University Community Service Team which is a manifestation of the implementation of life skills or entrepreneurship education programs in the rural spectrum with a regional approach, namely rural areas and other relevant parties when conducting skills training activities in the framework of banana cultivation and training in the processing of original products into other products that have higher economic value and selling power and marketing management. Through the Community Service program is expected to form other small business groups that are able to utilize the potential of resources and local wisdom to increase family income which will have a positive impact on the level of citizens' welfare by fostering the spirit of entrepreneurship and creativity of citizens.